The interface between competition law and consumer protection : a Malaysian perspective - Abdul Rahman, Nasarudin; Amin, Naemah; Ahamat, Haniff (AENSI Publications, 2014)
Competition law and consumer protection share a common goal: how to benefit consumers. In this way, they are complementary and if applied properly they reinforce each other. Even though both share a common goal, the ways they achieve this goal are different. These differences pose opportunities and challenges.This paper aims to explore the interaction between competition law and consumer protection from the Malaysian perspective. The result of this study shows that there is a positive relationship between competition law and consumer protection in Malaysia. However, there are instances where they are inconsistent with each other. Therefore, it is very important to understand how competition law and consumer protection interact with each other so as to ensure that they do not work at cross purpose.